Molecular and Clinical Aspects of COVID-19 Vaccines and Other Therapeutic Interventions Apropos Emerging Variants of Concern - Islam, Khursheed Ul; A-Elgadir, Thoraya Mohamed Elhassan; Afaq, Sarah; Ahmad, Tanveer; Iqbal, Jawed (Frontiers in Pharmacology, 2021)
Coronavirus disease 2019 (COVID-19) has overwhelmed the healthcare and economy of the world, with emerging new variants of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) posing an everlasting threat to humanity. While most COVID-19 vaccines provide adequate protective immunological response against the original SARS-CoV-2 variant, there is a pressing need to understand their biological and clinical responses. Recent evidence suggests that some of the new variants of SARS-CoV-2 evade the protection conferred by the existing vaccines, which may impede the ongoing efforts to expedite the vaccination programs worldwide. These concerns have also highlighted the importance of a pan-COVID-19 vaccine, which is currently in the making. Thus, it is imperative to have a better molecular and clinical understanding of the various COVID-19 vaccines and their immunological trajectory against any emerging variant of concerns (VOCs) in particular to break this vicious cycle. Furthermore, other treatment regimens based on cellular therapies and monoclonal antibodies should be explored systematically as an alternative and readily available option considering the possibility of the emergence of more virulent SARS-CoV-2 mutants. In this review, we shed light on the various molecular mechanisms and clinical responses of COVID-19 vaccines. Importantly, we review the recent findings of their long-term immune protection and efficacy against emerging VOCs. Considering that other targeted and effective treatments will complement vaccine therapy, we provide a comprehensive understanding of the role of cell-based therapies, monoclonal antibodies, and immunomodulatory agents as alternative and readily available treatment modalities against any emerging SARS-CoV-2 variant.